Heat Treatment Research Studies of EN9 Carbon Steel by Quenching Operation in Different Quenching Media - T.R. Vijayaram; S. Nithish; D. Ananthapadmanaban (International Journal of Mechanical Dynamics and Systems Analysis, 2024)
In this experimental research, EN9 type of steels is selected to process the heat treatment by quenching to increase the hardenability of a material. EN9 steel is cut into small work samples with diameter 25mm and length 15mm to analyze. Then they are polished the cut surface in a fine manner. Microstructure and hardness are to be found for EN9 work pieces before heat treatment at different locations like at origin, 2.5 mm, 5 mm, 7.5 mm and 10 mm from origin. The cut work pieces are then placed in muffle furnace and heated at 810º–840º, predetermined temperature range with soaking time 40 minutes. Then once they are heated, immediately they are quenched in different quenching medium with different concentrations in a vessel by using tongs. In this research work, quenching medium chosen are water, oil, brine solution with different concentration and Poly Vinyl Alcohol (PVA), a polymer quenchant with different concentration. Then the microstructure and hardness is compared for EN9 material before heat treatment and after heat treatment with different quenching media to obtain the result. Graphs like location Vs hardness and quenching media Vs average hardness were drawn.
Keywords: Brine solution; EN9; Heat treatment; Oil; Poly Vinyl Alcohol; water